2013
DOI: 10.1089/ast.2012.0944
|View full text |Cite
|
Sign up to set email alerts
|

A Potential Gravity-Sensing Role of Vascular Smooth Muscle Cell Glycocalyx in Altered Gravitational Stimulation

Abstract: Previously, we have shown that vascular smooth muscle cells (VSMCs) exhibit varied physiological responses when exposed to altered gravitational conditions. In the present study, we focused on elucidating whether the cell surface glycocalyx could be a potential gravity sensor. For this purpose, a roller culture apparatus was used with the intent to provide altered gravitational conditions to cultured rat aortic smooth muscle cells (RASMCs). Heparinase III (Hep.III) was applied to degrade cell surface heparan s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Analysis of the force curves allows measurement of glycocalyx thickness, which was significantly less for TRF2‐overexpressing cells than GFP‐expressing cells (Fig B, right panel). To investigate whether these global changes in glycocalyx structure are responsible for the immunosuppressive role of TRF2, we globally inhibited glycocalyx and HS synthesis in cancer cells using sodium chlorate (Kang et al , ). As expected, treatment with sodium chlorate was sufficient to inhibit the presence of cell‐surface HS (Appendix Fig S2B and C).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the force curves allows measurement of glycocalyx thickness, which was significantly less for TRF2‐overexpressing cells than GFP‐expressing cells (Fig B, right panel). To investigate whether these global changes in glycocalyx structure are responsible for the immunosuppressive role of TRF2, we globally inhibited glycocalyx and HS synthesis in cancer cells using sodium chlorate (Kang et al , ). As expected, treatment with sodium chlorate was sufficient to inhibit the presence of cell‐surface HS (Appendix Fig S2B and C).…”
Section: Resultsmentioning
confidence: 99%
“…Kang et al . also observed HS proteoglycan (HSPG) on the surface of rat aortic artery SMCs cultured on a two‐dimensional (2D) surface by fluorescence microscopy but did not report GCX thickness. Qazi et al .…”
Section: The Gcxmentioning
confidence: 97%
“…Kang et al [13] also observed HS proteoglycan (HSPG) on the surface of rat aortic artery SMCs cultured on a two-dimensional (2D) surface by fluorescence microscopy but did not report GCX thickness. Qazi et al [14] imaged HS on the surface of SMCs suspended in a threedimensional (3D) collagen I gel using confocal microscopy and showed a clear surface GCX layer of about 1 lm thickness.…”
Section: The Gcxmentioning
confidence: 99%
“…While striving to develop GCX regeneration approaches, researchers are also in search of ways to clinically assess the EC GCX thickness, volume, and molecular composition for diagnostic purposes in order to evaluate therapeutic efficacy. Toward this aim, researchers have employed numerous methods that vary widely based on the study environment. This review will summarize animal and human studies that employ GCX imaging techniques such as orthogonal phase spectroscopy (OPS) and sidestream dark-field (SDF) imaging. ,, ,, These techniques have merit but are limited in their ability to precisely quantify the presence of the GCX as possible via microscopic methods that are commonly used for in vitro and ex vivo detection of the EC GCX. , ,,, Herein, we call for the development of clinically relevant detection methods that provide the precision offered by in vitro methods.…”
Section: Introductionmentioning
confidence: 99%